Management of Da'i Extracurricular Activities in Improving the Soft Skills of Male Students of Islamic Boarding Schools - Nur Maghfiroh; Abdullah Aminuddin Aziz (Jurnal Manajemen Pendidikan Islam Darussalam, 2025)
The management of da'i extracurricular activities plays an important role in improving the soft skills of students in Islamic boarding schools. The purpose of this study is to analyze the management of da'i extracurricular activities for male students, identify the soft skills possessed by students, and evaluate the influence of da'i extracurricular activities on improving the soft skills of male students at Tebuireng Islamic Boarding School, Jombang. The research method uses a qualitative approach with a case study type, data collection techniques through observation, interviews, and documentation, and data analysis using data reduction, data presentation, and drawing conclusions with data validity through triangulation of sources, time, and techniques. The results of the study indicate that da'i extracurricular activities are carried out through careful planning, clear organization, mobilization that encourages the improvement of soft skills, and continuous supervision; the students' soft skills include good communication, cooperation, leadership, empathy, and emotional intelligence; and structured da'i extracurricular activities effectively improve the communication skills, morals, empathy, cooperation, leadership, and creativity of students. The conclusion of this study is that structured and systematic management of da'i extracurricular activities is the main key in creating a learning environment that supports the development of character and social competence of male students at the Tebuireng Islamic Boarding School in Jombang. Recommendations from the results of this study include that the boarding school should further optimize managerial support for da'i extracurricular programs, provide further training for instructors, and collaborate with external agencies to expand the scope of coaching and development of students' soft skills.